1996
DOI: 10.1002/j.1460-2075.1996.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of putative activator-target affinities predicts transcriptional activating potentials.

Abstract: We quantitate the ‘activating potentials’ of deletion and point mutation variants of a 42 amino acid yeast transcriptional activating region excised from the yeast activator GAL4 and, using surface plasmon resonance, we measure the relative affinities of these molecules for a variety of proteins, including plausible target proteins as well as GAL80, a specific inhibitor of GAL4. We find a remarkable correlation between the relative activating potentials of the derivatives and their relative affinities for yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
205
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(216 citation statements)
references
References 50 publications
11
205
0
Order By: Relevance
“…Although smaller MTDs of 17 and 13 residues have been reported for Gal4p and Gln3p, respectively (46,47), transactivation domains of mammalian activators are reported to be large (48 -50). Using c-myc as a model, it has been suggested that a large transactivation domain is needed for interactions with TBP (51).…”
Section: Discussionmentioning
confidence: 93%
“…Although smaller MTDs of 17 and 13 residues have been reported for Gal4p and Gln3p, respectively (46,47), transactivation domains of mammalian activators are reported to be large (48 -50). Using c-myc as a model, it has been suggested that a large transactivation domain is needed for interactions with TBP (51).…”
Section: Discussionmentioning
confidence: 93%
“…Galactose induction of the GAL genes is initiated by ATP-dependent interaction of galactose with Gal3p, which then forms a complex with the negative regulator Gal80p (Platt and Reece 1998). This releases the positive transcriptional regulator Gal4p from Gal80p control and allows it to activate transcription of the GAL1, GAL2, GAL7 and GAL10 genes that contain the upstream activation sequences (UAS GAL ) in their promoter regions (Leuther and Johnston 1992;Wu et al 1996). Presence of glucose causes a virtually complete transcriptional repression of the GAL genes and thereby effectively shuts down galactose metabolism (Johnston et al 1994).…”
Section: Fermentation Of Hexoses By Saccharomyces Cerevisiaementioning
confidence: 99%
“…The well-characterized acidic activator Gal4 is responsible for the transcriptional stimulation of GAL genes, such as GAL1, which contain Gal4-binding sites in their promoters (Johnston 1987;Johnston and Carlson 1992;Dudley et al 1999). A variety of transcriptional components have been proposed to be the target of Gal4 including TBP (Melcher and Johnston 1995;Wu et al 1996), TFIIB (Wu et al 1996), Srb4 (Koh et al 1998;Park et al 2000), Gal11 (Jeong et al 2001), the Swi/Snf complex (Neely et al 2002), and the SAGA (Spt/Ada/ Gcn5/acetyltransferase) complex (Bhaumik and Green 2001;Brown et al 2001;Larschan and Winston 2001). These proposals are based on either in vitro protein interaction studies or inferences from various indirect in vivo experiments, and to date there is no definitive evidence that Gal4 directly interacts with any of these putative targets in vivo.…”
mentioning
confidence: 99%